2015
DOI: 10.1038/ncomms9212
|View full text |Cite
|
Sign up to set email alerts
|

Outbred genome sequencing and CRISPR/Cas9 gene editing in butterflies

Abstract: Butterflies are exceptionally diverse but their potential as an experimental system has been limited by the difficulty of deciphering heterozygous genomes and a lack of genetic manipulation technology. Here we use a hybrid assembly approach to construct high quality reference genomes for Papilio xuthus (contig and scaffold N50: 492 Kb, 3.4 Mb) and P. machaon (contig and scaffold N50: 81 Kb, 1.15 Mb), highly heterozygous species that differ in host plant affiliations and adult and larval color patterns. Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 58 publications
5
165
2
2
Order By: Relevance
“…Although we have not rigorously quantified this effect, after extensive work with pigmentation genes in V. cardui, we found that injecting earlier (e.g., at 1 h) typically produces more and larger mutant clones compared to injection performed later (e.g., at 4 h). This is consistent with previous studies that have found a higher deletion frequency when embryos are injected at earlier versus later stages (Li et al 2015a). Thus, for most of our deletion experiments, we aim to inject~1-2 h after oviposition.…”
Section: Embryo Injectionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although we have not rigorously quantified this effect, after extensive work with pigmentation genes in V. cardui, we found that injecting earlier (e.g., at 1 h) typically produces more and larger mutant clones compared to injection performed later (e.g., at 4 h). This is consistent with previous studies that have found a higher deletion frequency when embryos are injected at earlier versus later stages (Li et al 2015a). Thus, for most of our deletion experiments, we aim to inject~1-2 h after oviposition.…”
Section: Embryo Injectionsupporting
confidence: 83%
“…Unfortunately, to our knowledge, these remain the only two examples of lepidopteran knockins outside of the new data we present below. The first example of Cas9 genome editing in a species besides B. mori was described by Li et al (2015a), who produced deletions in three genes in the swallowtail butterfly Papilio xuthus. This was an important case study because it showed that the general approach used by Wang et al (2013) in B. mori could be transferred to other species and still retain the same level of high efficiency.…”
Section: Published Examples Of Cas9-mediated Genome Editing In Lepidomentioning
confidence: 99%
“…We obtained peptides and genome sequences for B. mori 66 , Papilio xuthus 67 and H. melpomene 11 . If a gene had more than one transcript, only the first transcript in the annotation was used.…”
Section: Syntenic Comparisonmentioning
confidence: 99%
“…Molecular bases underlying color pattern formation and its evolution in dragonflies are just as fascinating and challenging as in butterflies. Recently, effective RNAi-and genome-editing methods have been developed for gene functional analyses in butterflies (Ando and Fujiwara 2013;Nishikawa et al 2015;Li et al 2015;Perry et al 2016;Zhang and Reed 2016;Beldade and Peralta 2017). Applying these methods to dragonflies will be an important step toward future studies in this field (Okude et al 2017).…”
Section: Conclusion and Perspectivementioning
confidence: 99%